Assessment of hospitalisation costs and their determinants among Covid-19 patients in South Central Ethiopia - Abdene Weya Kaso; Esmael Mohammed; Gebi Agero; Gemechu Churiso; Taha Kaso; Helen Ali Ewune; Alemayehu Hailu (BMC Health Services Research, 2023)
Abstract Background The coronavirus disease 2019 (Covid-19) pandemic is a global public health problem. The Covid-19 pandemic has had a substantial impact on the economy of developing countries, including Ethiopia.This study aimed to determine the hospitalisation costs of Covid-19 and the factors associated with the high cost of hospitalisation in South Central Ethiopia. Methods A retrospective cost analysis of Covid-19 patients hospitalised between July 2020 and July 2021 at Bokoji Hospital Covid-19 Treatment Centre was conducted using both the micro-costing and top-down approaches from the health system perspective. This analysis used cost data obtained from administrative reports, the financial reports of the treatment centre, procurement invoices and the Covid-19 standard treatment guidelines. The Student’s t-test, Mann-Whitney U test or Kruskal-Wallis test was employed to test the difference between sociodemographic and clinical factors when appropriate.To identify the determinants of cost drivers in the study population, a generalised linear model with gamma distribution and log link with a stepwise algorithm were used. Results A total of 692 Covid-19 patients were included in the costing analysis. In this study, the mean cost of Covid-19–infected patients with no symptoms was US$1,073.86, with mild symptoms US$1,100.74, with moderate symptoms US$1,394.74 and in severe–critically ill condition US$1,708.05.The overall mean cost was US$1,382.50(95% CI: 1,360.60–1,404.40) per treated episode.The highest mean cost was observed for personnel, accounting for 64.0% of the overall cost. Older age, pre-existing diseases, advanced disease severity at admission, admission to the intensive care unit, prolonged stay on treatment and intranasal oxygen support were strongly associated with higher costs. Conclusions This study found that the clinical management of Covid-19 patients incurred significant expenses to the health system. Factors such as older age, disease severity, presence of comorbidities, use of inhalation oxygen therapy and prolonged hospital stay were associated with higher hospitalisation costs.Therefore, the government should give priority to the elderly and those with comorbidities in the provision of vaccination to reduce the financial burden on health facilities and health systems in terms of resource utilisation.